A novel poly(vinyl alcohol) post-precipitation template synthesis and property tuning of photoactive mesoporous nano-TiO2 - Hamisu, Abubakar; Gaya, Umar; Abdullah, Abdul Halim (Iranian Chemical Society, 2020)
For the first time, a facile method is introduced to obtain ultrathin, mesoporous TiO2 nanosheets by the alkali precipitation of aqueous TiCl3 in the presence of NH4OH, and in-situ templating with polyvinyl alcohol (PVA). The synthesized titania have been characterized by N2 adsorption-desorption measurements, x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermo-gravimetric analysis (TGA) and ultraviolet-visible (UV-vis) spectroscopy. The obtained titania were hexagonal-like, detached, non-agglomerated, polydispersed, sub-20 nm nanodiscs. Unlike in doping methods, their surface area and pore volumes of can easily be tailored devoid of any wavelength shift, by simply tuning the amount of the template. Accordingly, their aggregation as microspheres can successfully be controlled by the templating step. The remarkable photoactivity of these nanoscopic materials has been confirmed by the degradation of aqueous methyl orange.